The Clinical/Practicum Experience in Professional Preparation: Preliminary findings - Ralph, Edwin; Walker, Keith; Wimmer, Randy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2008)
AbstractThe authors synthesize preliminary findings from an interdisciplinary study of the practicum/clinical phase of undergraduate pre-service education in the professions. Early data analysis identified similarities and differences across disciplines in terms of: (a) the terminology describing each practicum program, (b) the programs’ key characteristics, (c) their respective strengths and weaknesses, (c) the way practicum students are mentored and evaluated, and (d) future innovations in this experiential learning phase of professional preparation.